Diseño de portales evitando o reduciendo el corte en rocas. (2017)
Geometrical alignment conditions as well as topography restrictions lead to portal designs, which do not necessarily intersect the ground in a desired perpendicular angle. Lack of portal design guidelines and a vague understanding on the rock mass yields, therefore, to conservative (heavy/stiff support) portal designs, complex construction procedures, longer construction time and a higher environmental impact. The present work proposes a new approach for skewed portal design based on a complete understanding of the rock mass behavior and its failure mechanisms. The approach is based on 2D numerical models and complemented with 3D model for comparison and optimization. A study case in the Andes range is presented, where conventional and skewed portals have been constructed.